2023
DOI: 10.3389/fimmu.2022.1044678
|View full text |Cite
|
Sign up to set email alerts
|

Serplulimab plus chemotherapy as first-line treatment for extensive-stage small-cell lung cancer: A cost-effectiveness analysis

Abstract: IntroductionThe ASTRUM-005 trial (NCT04063163) revealed that combination serplulimab plus chemotherapy (etoposide and carboplatin [EC]) treatment was associated with survival advantages relative to chemotherapy alone in patients diagnosed with extensive-stage small-cell lung cancer (ES-SCLC). As these immuno-chemotherapeutic regimens are extremely expensive, however, it is critical that the relative cost-effectiveness of combination serplulimab and chemotherapy treatment as a first-line treatment for ES-SCLC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Due to the considerable price advantage and accessibility, sintilimab and camrelizumab plus chemotherapy may be appropriate alternatives for advanced ESCC patients. Serplulimab, a novel domestic PD-1 inhibitor, plus chemotherapy for first-line treatment has not shown an economic advantage, although it may be cost-effective in patients with extensive-stage small cell lung cancer (Zhu et al, 2022b). Therefore, a substantial price reduction for serplulimab was essential to improve patient affordability.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the considerable price advantage and accessibility, sintilimab and camrelizumab plus chemotherapy may be appropriate alternatives for advanced ESCC patients. Serplulimab, a novel domestic PD-1 inhibitor, plus chemotherapy for first-line treatment has not shown an economic advantage, although it may be cost-effective in patients with extensive-stage small cell lung cancer (Zhu et al, 2022b). Therefore, a substantial price reduction for serplulimab was essential to improve patient affordability.…”
Section: Discussionmentioning
confidence: 99%
“…Several cost‐effectiveness analyses have been performed, 30–33 and most of them showed that the addition of immunotherapy to chemotherapy is not cost‐effective for SCLC patients. One exception is the addition of serplulimab to chemotherapy, which was shown to be cost‐effective in a recent analysis 34 …”
Section: Discussionmentioning
confidence: 99%
“…17,18 A frequency network meta-analysis was then selected to perform indirect comparisons, with HR values associated with the durvalumab plus GemCis versus pembrolizumab plus GemCis regimens (.92 [.73-1.15] and .86 [.69-1.07]) (Table 1) being derived using a fixed-effects meta-regression model (Table 1). [18][19][20] Model construction, data extraction and parameter calculations were respectively performed with TreeAge Pro 2022, GetData Graph Digitizer (v 2.26) and the 'netmeta' package in Rstudio (v 1.2.5042).…”
Section: Model Structure and Survivalmentioning
confidence: 99%
“…22 Grade 3 or higher treatment-associated adverse events (AEs) were assigned a mean disutility value of .073 as a means of assessing deteriorating patient QoL (Table 1). [17][18][19][22][23][24][25] The present study considered direct costs, including the costs of drugs, administration, laboratory testing, imaging, grade 3 or higher AE management (for AEs with ≥5% incidence), BSC and terminal care (Table 1). Real-world hospital data and information from the Centers for Medicare & Medicaid Services were used to determine drug costs.…”
Section: Utilities and Costsmentioning
confidence: 99%
See 1 more Smart Citation